Effect of Ecological, Economic and Social Factors on Environmental Conservation of Dam Reservoirs for Hydroelectric Power - Supriyono, Supriyono; Mafruhah, Izza; Prasetyani, Dwi (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to determine the mapping of water catchment areas as a basis for environmental conservation concerns, and to analyze ecological, economic and social factors that influence the stakeholder’s capacity for conservation responses. The method used in this research is a mixed method and data analysis was conducted by using Global Information System (GIS) analysis and multiple regression. The results showed that all determinants have significant effects on conservation concern (coefficient = 0.635, p-value= 0.000). Meanwhile, the testing of moderation effect with conservation concern showed an insignificant effect (coefficient =0.042, p-value= 0.545). The analysis of the variable of distance as mediating variable on conservation concern also showed the insignificant results (coefficient = - 0.113, p-value =0.086). Moreover, the results of data analysis in this study based on GIS analysis showed a fairly rapid and concerning increase in sedimentation between 2013 and 2017. This would imply that quick efforts were needed to conserve dam reservoirs. In the social factor, the conditions imply to improve their participation through ecotourism. The findings highlight the importance for stakeholders to encourage the implementation of conservation and ecotourism of dam environment.